Study of Public Exposure to Microwave Propagation from Current Cell Phones - mohsen aliabadi; hosna hatami; mozhgan ardestani; maryam farhadian (طب کار)
Background: Due to the increase of public concern about the physical and psychological effects of radiation on the health of cell phone users, the present study aimed to determine public exposure to microwave propagation from current cell phones in different user conditions. Methods: In this cross-sectional study, the effective intensity of microwave radiation from cell phone were measured in different user conditions during call establishment, conversion, short massage and Bluetooth. Microwave meter HI 2200 model made by Holaday Co. was used to measure radiation according to the standard method No.C93.5. Shielding effectiveness of anti radiation covers for cell phone during call establishment was also determined. Results: The effective intensities of microwave radiation emitted from cell phones were equaled to 51.4±31.6μW/cm2,42.7±30.9μW/cm2,8.6±7.1μW/cm2,1.3±0.2 μW/cm2 during call establishment, conversion, short massage and Bluetooth, respectively which were lower than the exposure limits. There was not statistical significance between intensities of microwave radiation of cell phones based on the maker companies (Pvalue >0.05). Correlation between specific absorption rate and microwave intensity of cell phones were significant (Pvalue<0.01). Conclusion: Although the microwave intensities of cell phones was lower than the exposure limits, however, due to the failure to obtain conclusive evidence on the health effects of radiation exposure on humans, it seems to be necessary to inform users about health risks , reduce conversation time as possible and use standard cell phone covers.